Ownership Structure and Earnings Quality of Listed Financial Firms in Nigeria (Global Journal of Management and Business Research, 2020)
The study determined the effect of ownership structure on earnings quality of listed financial firms in Nigeria. The study employed secondary data. The study population comprised all the 16 listed financial firms on the Nigerian Stock Exchange. Purposive sampling technique was adopted to select top 10 banks whose shares are consistently traded on the stock market. Data for ownership structure and earnings quality were sourced from the audited financial statements of the selected firms and the Nigerian Stock Exchange Fact book over a period of 10 years (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). Collected data were analyzed using pooled ordinary least square, fixed effect and random effect estimation techniques. The result from the study showed that institutional ownership (t=4.3, p˂0.05) had a positive and statistically significant relationship with earnings quality while ownership concentration (t=-2.5, p˂0.05) had a negative and significant relationship with earnings quality.
Keywords: ownership concentration; institutional ownership; managerial ownership; earnings quality